5 - Nigeria’s Foreign and Defence Policies During Babangida’s Regime: An Assessment - Jemirade, Dele (Africa Development, 2021)
This article investigates the changes to and achievements of Nigeria’s foreign and defence policies from 1985 to 1993. It also examines the economic, political, and sociocultural implications of these policies on the nation. The article argues that despite some identified failures of Ibrahim Babangida’s regime, certain innovations and actions, especially the foreign and defence policies that were introduced and carried out by his government, were significant in nature. The article also addresses the interlocking relationship between defence and foreign policy execution and concludes with recommendations on how this can be managed to promote the effectiveness of Nigeria’s external relations. The article depended largely on archival materials from the Nigerian Institute of International Affairs, supported by scholarly journal articles, books and newspaper materials.